Binding interaction of a novel fluorophore with serum albumins: steady state fluorescence perturbation and molecular modeling analysis - Pal, Uttam (Springerplus, 2015)
Fluorescence emission and anisotropy are widely used to measure the binding parameters and kinetic behavior of reactions that cause a change in the rotational time of a fluorescent molecule. We report here fluorescence emission and anisotropy behavior of a newly synthesized novel naphthalene base fluorophore (methyl 3-[(6-{[2-(tert-butoxy)-2-oxoethyl] (4-methoxyphenyl)amino}naphthalen-2-yl)formamido]propanoate) in several solution conditions including its binding to human and bovine serum albumin proteins both in their native and denatured states. The fluorescence yield of the compound substantially increased inside hydrophobic protein surface and ~30 nm decrease in Stokes’ shift, compared to aqueous solution, was observed. Shift in fluorescence excitation peak position from the absorption peak of the molecule was ~8 nm in protein solution. This indicated possible alteration of excited state geometry of the compound by the globular fold of albumins. In addition, we measured the steady state fluorescence anisotropy of the molecule to evaluate several thermodynamic parameters and the results suggested the binding was energetically favorable. The measured ΔG° was ~−30 kJ mol(−1) and the derived dissociation constant was ~10(−6) M. The molecular docking analysis further highlighted the nonspecific association of the compound with the proteins and hydrophobic forces may have a significant role in the binding processes. Under the denatured condition of the protein, the compound lost its binding efficacy and reduction in fluorescence intensity was observed. Thus, the molecule appears as a new fluorescence probe to report the nature of its binding site in terms of increased fluorescence quantum yield and decreased Stokes’ shift. It can also report the changes in the binding site due to global change in protein structure such as unfolding/misfolding often linked to several human disorder. Further it could be useful to detect and study the drug binding site of specific protein of interest. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-015-1333-8) contains supplementary material, which is available to authorized users.